Double Power-Law in Leucosome Width Distribution: Implications for Recognizing Melt Movement in Migmatites - Saukko, Anna; Ahläng, Christian; Nikkilä, Kaisa; Soesoo, Alvar; Eklund, Olav (Frontiers in Earth Science, 2020)
Leucosome sizes in migmatites has been shown to follow power-law distribution, which is indicative of self-organized criticality governing accumulation and transport of partial melts in anatexis. In our measurements of leucosome widths in the Olkiluoto migmatite in western Finland, we found double power-law distributions in addition to single power-law distributions. We divided the double power-law behaviors into those with positive and negative kinks separating the two power-law regimes. We propose that double power-law distributions in migmatites result from impediments on the bottom-up self-organized criticality that melt transport processes commonly display. These impediments can be caused by some leucosomes solidifying before others, in which case the leucosomes were effectively formed in two distinct events or phases. We also consider the emergence of double power-laws as a result of melt accumulation in and sudden melt removal from conduits of a specific size.